Artificial Grammar Learning in Dyslexic and Nondyslexic Adults: Implications for Orthographic Learning. (2nd January 2017) - Samara, Anna; Caravolas, Markéta
ABSTRACT: Potential implicit orthographic learning deficits were investigated in adults with dyslexia. An artificial grammar learning paradigm served to assess dyslexic and typical readers' ability to exploit information about chunk frequency, letter-position patterns, and specific string similarity, all of which have analogous constructs in real orthographies. We also investigated whether implicit learning deficits in dyslexia held for letter strings (Experiment 1) and symbol strings (Experiment 2). Experiment 1 results indicated that dyslexic adults were mildly impaired in memorizing letter strings, although this finding proved inconclusive in a more stringent analysis of the data across experiments. There were no signs of difficulty during symbol string memorization in Experiment 2. In each experiment, dyslexic and nondyslexic readers were comparably sensitive to chunk frequencies and showed reliable sensitivity to letter and shape position patterns and string similarities. These findings challenge the claim that a general learning deficit contributes to literacy difficulties in dyslexia.